STREAMLINE ANALYSIS OF SYMPTOMS OF CYCLONES IN NORTH SUMATRA (STUDY OF CASE : 1-10 SEPTEMBER) - Guchi, Novaldo; Lubis, Lailatul Husna (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study aims to analyze the cyclonic disturbance streamlined on the surface temperature in the North Sumatra region. The data used in this streamlined analysis is accessed from the websitehttp://ww.bom.gov.au/ and analyzed to see cyclonic disturbances in the area and any impacts that occur due to cyclonic disturbances in the area. This cyclonic disturbance is caused by wind speed, where wind speed is one of the causes of increasing water vapor in the atmosphere. Judging from its geographical location, the North Sumatra region is one of the provinces located in the western part of Indonesia, located on the line 1 ̊ ̶ 4 ̊ north lattitude and 98 ̊ ̶ 100 ̊ east longitude. The North Sumatra region is one of the many areas affected by cyclonic disturbances. Weather disturbances such as tropical cyclones can change atmospheric conditions in the area where a tropical cyclone is passing or is traversed and changes in surface temperatures traversed by the tropical cyclone. Based on sea surface temperature data obtained from the BMKG website https://dataonline.bmkg.go.id and obtained from these data that the surface temperature intensity in the North Sumatra region is at a temperature of 26.3ºC-28.3ºC.